Social marketing in the 21st century - Andreasen, Alan R. 1934- (SAGE Publications, 2006)
"The goal of this cutting-edge book is to reposition social marketing so that foundations, government agencies, and various nonprofits will approach social change in a way that reaches both upstream and downstream individuals in society. Author Alan R. Andreasen outlines potential roles, restates fundamental principles, and then suggests how social marketing might be applied to a sample of nontraditional challenges"--BOOK JACKET.